Plea Bargaining as a Mean to Maximum Sentence - Kim, Jung wook (KDI Journal of Economic Policy, 2013)
This paper outlines the findings of a model of plea bargaining with multiple defendants, in which a prosecutor makes plea offer sequentially. It is shown that plea discount can be minimized with sequential offers and that not all of defendants shall be induced to plead guilty. By allowing sequential offer, a prosecutor has more power in the plea bargaining, which may increase social welfare by giving appropriate level of punishment to the guilty.